2021
DOI: 10.3390/s21134564
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Vehicle and Pedestrian Activity from Town and City Traffic Cameras

Abstract: Traffic cameras are a widely available source of open data that offer tremendous value to public authorities by providing real-time statistics to understand and monitor the activity levels of local populations and their responses to policy interventions such as those seen during the COrona VIrus Disease 2019 (COVID-19) pandemic. This paper presents an end-to-end solution based on the Google Cloud Platform with scalable processing capability to deal with large volumes of traffic camera data across the UK in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Improving uptake of health protective behaviours is an important public health challenge, not only for COVID-19, but for infectious disease prevention more widely. Face coverings, hand hygiene and maintaining physical distance have all been identified as effective infection control strategies that have relatively few downsides in comparison to more far-reaching interventions such as society-wide ‘lockdowns’ [ 11 ]. Identifying ways to achieve good adherence to such measures requires that we are first able to measure adherence accurately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving uptake of health protective behaviours is an important public health challenge, not only for COVID-19, but for infectious disease prevention more widely. Face coverings, hand hygiene and maintaining physical distance have all been identified as effective infection control strategies that have relatively few downsides in comparison to more far-reaching interventions such as society-wide ‘lockdowns’ [ 11 ]. Identifying ways to achieve good adherence to such measures requires that we are first able to measure adherence accurately.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19, regularly collected measures of behaviour that do not rely on self-report are rare. Notable exceptions include: mobility data based on mobile phone locations [ 10 ]; footfall data in city centres [ 11 ]; and official statistics on vaccine uptake based on electronic records [ 12 ]. Most of these examples relate to where people are located or whether they engage with health services.…”
Section: Introductionmentioning
confidence: 99%
“…Improving uptake of health protective behaviours is an important public health challenge, not only for COVID-19, but for infectious disease prevention more widely. Face coverings, hand hygiene and maintaining physical distance have all been identified as effective infection control strategies that have relatively few downsides in comparison to more far-reaching interventions such as society-wide ‘lockdowns.’ 12 Identifying ways to achieve good adherence to such measures requires that we are first able to measure adherence accurately. Though self-report can be a useful proxy for behaviour, our review suggests that academic research has become overly reliant on it, so much so that although we identified 27, 279 papers which included terms related to COVID-19 and to hand hygiene, face covering or social distancing, just 48 of these papers (<0.2%) actually studied the behaviour in question objectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19, regularly collected measures of behaviour that do not rely on self-report are rare. Notable exceptions include: mobility data based on mobile phone locations 11 ; footfall data in city centres 12 ; and official statistics on vaccine uptake based on electronic records 13 . Most of these examples relate to where people are located or whether they engage with health services.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to data-driven studies, we can find specific works on private vehicle and public transport that treat them separately, thus lacking of an integrated view. The former focuses on analyzing the impact of the pandemic and the subsequent restrictions on traffic flows as in [ 26 ] (Rome, Italy), [ 27 ] (Qatar), [ 28 ] (several locations in the UK), and [ 29 ] (Slovakia), and its positive effects on pollution [ 26 , 30 , 31 ], and accidents [ 32 ]. Among the works that study the pandemic’s impact particularly related with public transport using data-driven analyses, let us highlight the following research.…”
Section: Related Workmentioning
confidence: 99%